Urbanization in Transition: Building A Future-Ready Framework for Malaysia’s Sustainable Tiered City System - Yong Chee Kong; Noraini Omar Chong; Egna Francis Gitom; Theo Fidelis Tarigan (Journal of Environmental and Development Studies, 2026)
Malaysia’s urban transformation has entered a critical transitional phase characterized by rapid metropolitan expansion, uneven regional development, and evolving governance challenges. Although the national urbanization rate reached 75.8% in 2024, urban growth remains heavily concentrated within major conurbations, widening disparities between metropolitan centers and secondary cities. This study critically examines Malaysia’s tiered city system as a strategic framework for achieving more balanced, resilient, and sustainable urban development. The research adopts a mixed-method approach integrating spatial analysis, policy review, and expert-based validation. Spatial and demographic data from the Department of Statistics Malaysia (DOSM) and PLANMalaysia’s BMGN database were analyzed alongside key national planning policies, including the Fourth National Physical Plan (RFN4) and the Second National Urbanization Policy (DPN2). The study also incorporates comparative insights from international urban governance models and systems-based urban planning perspectives. The findings reveal persistent structural asymmetries within Malaysia’s urban hierarchy, reflected in fragmented governance, uneven spatial intensity, limited functional specialization, and weak integration between urban tiers. In response, the study proposes the Future-Ready Tiered City Framework (FRTCF), which integrates functional hierarchy, spatial intensity optimization, governance synchronization, digital intelligence systems, and resilience-oriented planning principles. This paper introduces a future-ready, adaptive framework that bridges hierarchical planning and network-based urban governance in the Global South, supporting more inclusive, data-driven, and sustainable urban transformation.